Endogenous fertility and intergenerational transfers: The significance of the sibship size effect - Elise S. Brezis; Rodolphe Dos Santos Ferreira (Bar-Ilan University, Department of Economics, 2012)
Since the seminal work of Becker, the analysis of endogenous fertility has been based on the trade-off faced by parents between the quantity and the quality of their children. In order to have an interior solution, the model assumes that in case children work, still they get positive income from their parents. However, in some developing countries, child labor is necessary as a source of income. The purpose of this paper is to adapt the quantity-quality trade-off of the Beckerian model for the cases where net transfers are in fact from children to parents. The paper shows that by adding a sibship size effect, we restore the possibility of the trade-off.
Keywords: J13; 330; Endogenous fertility; Intergenerational transfers; Human capital formation; Familienplanung; Kinderarbeit; Haushaltseinkommen; Intergenerationale Übertragung; Generationengerechtigkeit; Familienökonomik; Theorie